Evaluation of development potential and application prospect of geothermal resources: A case study of Xiangfu District in Kaifeng - SUN Guanyu, BAI Zongxian, LI Hongda, WANG Yufei, BAI Zonghan, GAO Huijie, ZHU Zhimin, HUANG Zheng, MA Yingliang, WANG Liangliang (Youqicang pingjia yu kaifa)
With the growing global demand for clean energy, geothermal resources as a renewable energy source have attracted widespread attention. This study evaluated the geothermal resource development potential and application prospects in the Xiangfu District of Kaifeng City. The results showed that the vertical temperature field of the thermal reservoir in the Xiangfu District could be divided into varying temperature zones, constant temperature zones, and increasing temperature zones, with depth significantly influencing the temperature distribution. The geothermal gradient increased with depth above 500 m and gradually decreased below 500 m. Chemical analysis of geothermal fluids showed significant differences in the water chemistry types between thermal reservoirs at different depths, with no significant hydraulic connection between the reservoirs. Based on the maximum allowable depth reduction method and the extracted water volume method, the total exploitable geothermal fluid without reinjection was estimated to be 9,390×104 m3. Under complete reinjection conditions, the total exploitable geothermal fluid was estimated to be 360.7×108 m3, indicating substantial development potential. These research findings provide a scientific basis and guidance for the efficient development and utilization of geothermal resources in the Xiangfu District.